2007
DOI: 10.1128/jb.00434-07
|View full text |Cite
|
Sign up to set email alerts
|

Complex Interplay between Type 1 Fimbrial Expression and Flagellum-Mediated Motility of Uropathogenic Escherichia coli

Abstract: Type 1 fimbriae and flagella have been previously shown to contribute to the virulence of uropathogenic Escherichia coli (UPEC) within the urinary tract. In this study, the relationship between motility and type 1 fimbrial expression was tested for UPEC strain CFT073 by examining the phenotypic effect of fimbrial expression on motility and the effect that induction of motility has on type 1 fimbrial expression. While constitutive expression of type 1 fimbriae resulted in a significant decrease in motility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 68 publications
7
86
0
Order By: Relevance
“…Flagellar synthesis is decreased in cells attached to plastic surfaces as compared with freeliving bacteria (Prigent-Combaret et al, 1999) as well as during microcolony formation on epithelial cells (Cleary et al, 2004). Constitutive expression of type 1 fimbriae, an essential virulence factor in UTIs (Connell et al, 1996), has been shown to decrease motility of UPEC (Bryan et al, 2006;Lane et al, 2007a), partially due to the abundance of fimbrial structures at the cell surface (Lane et al, 2007a). Subsequent screening of factors that participate in a decreased-motility phenotype identified four transcriptional regulators, LrhA, Lrp, SlyA and P fimbriae protein PapX, that partially restore motility without affecting type 1 fimbriae expression (Simms & Mobley, 2008a).…”
Section: Discussionmentioning
confidence: 99%
“…Flagellar synthesis is decreased in cells attached to plastic surfaces as compared with freeliving bacteria (Prigent-Combaret et al, 1999) as well as during microcolony formation on epithelial cells (Cleary et al, 2004). Constitutive expression of type 1 fimbriae, an essential virulence factor in UTIs (Connell et al, 1996), has been shown to decrease motility of UPEC (Bryan et al, 2006;Lane et al, 2007a), partially due to the abundance of fimbrial structures at the cell surface (Lane et al, 2007a). Subsequent screening of factors that participate in a decreased-motility phenotype identified four transcriptional regulators, LrhA, Lrp, SlyA and P fimbriae protein PapX, that partially restore motility without affecting type 1 fimbriae expression (Simms & Mobley, 2008a).…”
Section: Discussionmentioning
confidence: 99%
“…coli is the major causative agent in human UTIs, one of the most common bacterial infections. In most cases, uropathogenic clones are selected from the fecal flora, and the pathogenic potential of E. coli strains is thought to be dependent on the presence of VFs 19,23 . Based on their components and products called virulence factors, E. coli cells attach selectively to the mucosa uro-epithelium, promoting colonization and persisting in the urinary tract, inducing, then, a local inflammatory response and sometimes to promote tissue lesions 23,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Cystitis (lower UTI) is characterized by pelvic discomfort, especially pre -and immediately post void, frequent or urgent voiding and suprapubic pain. Acute pyelonephritis (upper UTI) is, most of the times, a more serious problem and is clinically identified by the fever, flank pain, nausea and, sometimes, vomiting 19,22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…To detect TosA, total protein from the tos deletion mutants, E. coli CFT073, or E. coli CFT073 carrying the pBAD overexpression constructs was collected and Western blotting was performed. Briefly, equal amounts of total proteins, determined using a Pierce BCA protein assay kit (Thermo Scientific), from specific constructs were resolved, transferred, and blotted with polyclonal anti-TosA antibodies (27), polyclonal antiFliC antibodies (37), or an anti-His 6 antibody (Invitrogen).…”
Section: Bioinformaticsmentioning
confidence: 99%
“…It is now recognized, however, that adherence genes and flagellar genes can be reciprocally coordinated (34)(35)(36)(37)(38)(39). In this network, it is logical that an adherent bacterium should not be motile and a motile bacterium should not be adherent.…”
mentioning
confidence: 99%